Effect of Chemical Treatments on Morphological, Physical and Mechanical Properties of Bamboo/Glass Fibers Hybrid Laminated Composite - Yudhanto, Ferriawan; Wisnujati, Andika; Yudha, Venditias; Rachmawati, Putri; Dantes, Kadek Rihendra (International Journal of Integrated Engineering, 2021)
Bamboo Apus (Gigantochloa apus) is a long wood fiber plant with a short planting period of 4-5 years that can be used as an alternative to reduce synthetic fibers in manufacturing composite products. The bamboo strips used to reinforce was prepared by alkali treatment in 5 wt.% NaOH (sodium hydroxide) at a temperature of 80oC for 2 hours, followed with a delignification (bleaching) of 3 wt.% H2O2, at a temperature of 60oC, PH=10 for 1 hour. The manufacturing of laminated composite products was carried out by the vacuum infusion (VI) method with a 0.8 bar pressure with a stacking sequence of 1 ply of the woven bamboo strip and 3 plies of chopped strand mat glass fiber. The tensile test of bamboo/glass fibers hybrid laminated composite treated (HLC-T) was increased by 78%, while the flexural test was increased by 73.6%. It shows that the removal of lignin and hemicellulose in the bamboo fibers due to chemical treatment could improve the compatibility between the fiber and polyester.